2012
DOI: 10.1371/journal.pone.0033487
|View full text |Cite
|
Sign up to set email alerts
|

Cold Physiology: Postprandial Blood Flow Dynamics and Metabolism in the Antarctic Fish Pagothenia borchgrevinki

Abstract: Previous studies on metabolic responses to feeding (i.e. the specific dynamic action, SDA) in Antarctic fishes living at temperatures below zero have reported long-lasting increases and small peak responses. We therefore hypothesized that the postprandial hyperemia also would be limited in the Antarctic fish Pagothenia borchgrevinki. The proportion of cardiac output directed to the splanchnic circulation in unfed fish was 18%, which is similar to temperate fish species. Contrary to our prediction, however, gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…In comparison with Hb + Antarctic notothenioids, our measurements of routine Q̇in C. aceratus (at 0.8°C, 26.6 ml min −1 kg −1 ) is not as divergent as previously reported. Indeed, routine Q̇is lower (29 ml min −1 kg −1 at −0.5°C: Axelsson et al, 1992), or only marginally higher (24 ml min −1 kg −1 at 0°C: Sandblom et al, 2012; 22 ml min −1 kg −1 at −1.0°C: Franklin et al, 2007), than that previously reported in smaller specimens of the more active, cryopelagic P. borchgrevinki. In a more typically benthic species, Trematomus bernacchii, routine Q̇was lower (17.6 ml min −1 kg −1 ; Axelsson et al, 1992).…”
Section: Evolutionary Consequences For the Loss Of Hbmentioning
confidence: 65%
“…In comparison with Hb + Antarctic notothenioids, our measurements of routine Q̇in C. aceratus (at 0.8°C, 26.6 ml min −1 kg −1 ) is not as divergent as previously reported. Indeed, routine Q̇is lower (29 ml min −1 kg −1 at −0.5°C: Axelsson et al, 1992), or only marginally higher (24 ml min −1 kg −1 at 0°C: Sandblom et al, 2012; 22 ml min −1 kg −1 at −1.0°C: Franklin et al, 2007), than that previously reported in smaller specimens of the more active, cryopelagic P. borchgrevinki. In a more typically benthic species, Trematomus bernacchii, routine Q̇was lower (17.6 ml min −1 kg −1 ; Axelsson et al, 1992).…”
Section: Evolutionary Consequences For the Loss Of Hbmentioning
confidence: 65%
“…When faced with an acute stressor, the GBF that normally accounts for 20–30% of cardiac output of an unfed fish, drastically drops. This response has been reported in several different species including O. mykiss (Axelsson & Fritsche, ; Gräns et al ., , ; Sandblom et al ., ) . We confirmed that this response was initiated when subjecting the fish to the standardized acute‐stress protocol that caused intestinal barrier dysfunction in O. mykiss .…”
Section: Discussionmentioning
confidence: 99%
“…The GBF under resting conditions maintained around 10-40% of cardiac output (Seth et al, 2011). However, during acute stress GBF is known to decrease drastically in various species of fish (Dupont-Prinet et al, 2009;Gräns et al, 2009aGräns et al, , 2009bSandblom et al, 2012) presumably as blood flow is prioritized to other oxygen demanding organs (e.g. brain and muscle tissues) during a fight-orflight response (Farrell et al, 2001;Seth et al, 2011).…”
Section: Funding Informationmentioning
confidence: 99%
“…The blood flow responses to food ingestion and digestion have been extensively characterized in the GI tract (144,164,166,171,280,281,514). This response, generally referred to as the postprandial hyperemia, has been described for a variety of species, including humans (325), monkeys (509), pigs (102), dogs (145,508), cats (127), rats (12), snakes (459), and fish (422,436). Studies in conscious animals have revealed a biphasic cardiovascular response to ingestion of a meal, with transient increases in aortic pressure, heart rate, and cardiac output, with either no change or a slight increase in GI blood flow noted during the anticipatory-ingestion phase of digestion (138,508).…”
Section: Small Intestine Functional Hyperemia (Postprandial Hyperemia)mentioning
confidence: 99%